Respiratory disease in cotton textile workers in the People's Republic of China. II. Pulmonary function results. - Christiani, David C.; Eisen, Ellen A.; Wegman, David H.; Ye, T. T.; Gong, Z. C.; Lu, P. L.; Dai, H. L. (Scandinavian Journal of Work, Environment & Health, 1986)
Pulmonary function tests were performed pre and post workshift on 887 textile workers with at least two years of employment in two cotton mills and one silk mill in Shanghai, the People's Republic of China. Environmental sampling was performed with vertical elutriators, and pulmonary function was performed with standardized techniques. Cotton textile workers were found to have greater across-shift decrements in forced expiratory volume in 1 s (FEV1.0) than silk workers. Increasing duration of exposure resulted in increasing acute decrements in FEV1.0, although significant acute decrements were found in workers with less than five years of exposure. The acute changes in FEV 1.0 were noted in both symptomatic and asymptomatic cotton workers, though the difference between the across-shift change in FEV1.0 (delta FEV1.0%) of the byssinotics and nonbyssinotics increased as work duration increased. There was no difference in preshift FEV1.0 between the cotton and silk workers, but several selection factors likely influenced the observations.